Study of thermo-mechanical properties of sugar palm fibre reinforced thermoplastic polyurethane composites for use as exterior material in automotive industry - Dandi, Bachtiar
The present work aimed to develop of sugar palm fibre (SPF) to reinforce thermoplastic polyurethane (TPU) composites. The extruder and the compression molding machine were used to fabricate this composite. Fibre surface treatment then conducted to enhance the properties of sugar palm fibre composites. Different factors are studied the optimization of processing, fibre size, and mixing ratio of SPF-TPU. Alkali, permanganate, and the microwave methods were used to enhance the surface properties to make it to have more adhesion between the fibre and polymer. Tensile, flexural, impact, properties and scanning electron microscope (SEM), thermogravimetric (TG), Fourier transform infrared (FTIR), and the energy dispersive X-ray (EDX) for SPF/TPU was tested. Composites of 10, 20, and 30% fibre loadings were fabricated and tested. Degradation behavior of the composites also be conducted by using accelerated weathering chamber follow the ASTM standard. This composite system could apply in automobile industry as reinforced plastic parts in different types of vehicles also produce friendly environment materials.